(untitled) (Comparative Professional Pedagogy, 2024)
This article addresses the pressing issue of fundamental training for future physics teachers, emphasizing the need to bridge theory and practice, integrate natural sciences with environmental education, and develop students’ research and environmental competencies. The focus is on the importance of collaborative project activities between educators and future physics teachers as a cornerstone of comprehensive training. The author introduces the project “Technology of Landscaping Educational Institutions” as a key method for environmental education during the fundamental training of physics teachers at a pedagogical university. Key project tasks included: 1) identifying ecological foundations for creating green spaces in educational institutions; 2) describing functional zones within the institution for potential improvements; 3) substantiating the roles of green spaces in the educational yard; 4) developing landscaping technology for the institution’s courtyard; and 5) exploring international landscaping practices through the example of Ariel University in Israel. The project was carried out through partnership pedagogy, cross-cultural communication, and inter-university cooperation between V.G. Korolenko Poltava National Pedagogical University and Ariel University. During the project, students, who are future physics teachers from V.G. Korolenko Poltava National Pedagogical University, engaged with scientific sources and the website of Ariel University. They participated in virtual tours of Ariel University’s campus and attended online consultations to assist with project tasks. As a result, Ukrainian students developed and presented reports on the technology of environmentalization for educational institutions and proposed their own landscape design concepts for the Poltava National Pedagogical University’s grounds. The project “Technology of Landscaping Educational Institutions” is a paragon of partnership pedagogy, cross-cultural communication, and inter-university collaboration. Knowing the nature, students become harmoniously developed and comprehensively aware personalities, which is an important element of modern educational process.